Building enduring smart city data platforms to provide urban management support: lessons learnt from UK Urban Observatories and the US Smart Columbus Operating System - Wolf, Kristina; Stiles, Jonathan; Miller, Harvey J.; Dawson, Richard J.; Mills, Jon P.; Blythe, Phil; Morley, Jeremy (Frontiers in Sustainable Cities, 2025)
Cities are complicated entities with multiple stakeholders operating data infrastructures complying to different regulations and standards in heterogeneous environments; this can be challenging when developing a smart city data platform to support cross-sector urban data management. Recent advances in Internet-of-Things technology can combine real-time data streams, such as weather sensors, traffic lights, cameras, and parking sensors, in a smart city data platform that supports city decision-making and enables new collaborations and knowledge production. This paper uses a case study methodology to analyze the Smart City Operating System (SCOS), part of a Smart City project awarded by the US Department of Transportation in 2016 in Columbus Ohio. SCOS was developed as a robust smart city data management platform. However, despite a well-designed organization, methodology, and processes, the platform did not sufficiently capture city users, and was no longer used soon after demonstration funding ended in 2021. We employ a literature review, project completion reports, key informant interviews, and a project evaluation to understand the value and limitations of SCOS and consider how it could have better captured city users. Our comparative analysis of the UK Observatories shows that their more restrained “living laboratory” vision, university support, and stable funding environment helped them endure, although they serve primarily as a research platform rather than a city management platform. To make recommendations for future city data platform projects, we discuss organizational and technical aspects of conducting smart city projects, including continuous stakeholder engagement, required data ownership and real-time data management support. The results aim to support city stakeholders in developing future data platforms and provide urban management support.